PENERAPAN MODEL WATERFALL DALAM SISTEM UJIAN SEKOLAH BERBASIS WEB PADA SMK WIRA BUANA I BOGOR - Jayusman Jayusman; Sri Wasiyanti (Jurnal Techno Nusa Mandiri, 2019)
Examination and repetition of activities such as midterm tests, semester tests and class increase examinations at SMK Wira Buana 1 Bogor are still manual, namely using paper, this is felt to be less effective because it takes a lot of costs, time, place and personnel in its implementation and still exists cheating students in carrying out the exam. In addition, the development of information technology and systems in the world of education is increasing, one example is the Computer Based National Examination (UNBK) also called the Computer Based Test (CBT), which is a system of implementing national examinations using computers as a test medium. This is the background of the author to make a web-based school exam information system there is SMK Wira Buana 1 Bogor. The method used in designing this web-based examination system is the waterfall method which is expected to be one of the breakthroughs in the running of the School Examination, both the Mid-Semester Examination and the Semester Final Examination which can reduce the operational costs of activities. The School Examination Information System becomes a medium for students to practice computer-based exams that can be accessed by all students of Bogor Wira Buana 1 Vocational School so that they can improve readiness and familiarize students in facing Computer-Based National Exams and provide convenience for schools in conducting examinations and providing speed in getting the test result score.